Integration of a Gas Switching Combustion (GSC) system in integrated gasification combined cycles. (November 2015) - Cloete, Schalk; Romano, Matteo C.; Chiesa, Paolo; Lozza, Giovanni; Amini, Shahriar
Highlights: GSC is a promising new reactor concept for CO2 capture with low energy penalty. The standalone fluidized bed reactors employed will allow for easy process scale-up. The simplest configuration achieves higher efficiencies than conventional solutions. Further increases in efficiency can be achieved via advanced heat management. The 41.9% maximum efficiency is in line with other CLC-IGCC configurations. Abstract: Chemical Looping Combustion (CLC) is a promising technology for achieving economically viable CO2 capture from fossil fuel energy conversion processes. However, complexities and costs surrounding the standard interconnected fluidized bed concept for CLC have prompted the investigation of alternative process configurations. This paper investigates one such configuration, Gas Switching Combustion (GSC), via combined reactor and process modelling. The GSC concept utilizes a standard bubbling/turbulent fluidized bed reactor where an oxygen carrier material is alternatively exposed to feeds of air and fuel (syngas from coal gasification in this case). This configuration maintains the good mixing characteristics of fluidized bed reactors while eliminating the solids handling challenges related to the standard dual fluidized bed system. It was shown that a cluster of GSC reactors operating in a well-controlled manner could supply sufficiently steady streams to a downstream gas turbine and CO2 purification and compression unit. The simplest configuration where fuel and air are fed alternatively to the reactors, with steam purging but no advanced heat management procedures returned a significantly higher electric efficiency (40.7%) than a baseline IGCC plant with currently available gas turbine and CO2 capture technology (35.3%), while also achieving slightly higher overall CO2 avoidance. It was also shown that there exists significant scope for trading further increases in electric efficiency for reductions in overall CO2 avoidance through adjustment of the reactor operating strategy. More complex purging and heat management strategies could further improve the electric efficiency to as high as 41.9%, with overall CO2 avoidance higher than 90%.